Elite Settlement dan Stabilitas Politik dalam Transisi Demokrasi Indonesia: Relasi Megawati Soekarnoputri dan Hamzah Haz Pasca-Krisis Politik 2001 - Roki Arbi; Aditya Perdana (Jurnal Noken: Ilmu-Ilmu Sosial, 2026)
This paper examines the 2001 political crisis, which culminated in the impeachment of President Abdurrahman Wahid, as a pivotal moment in Indonesia’s post-Reformasi democratic transition. The main issue examined is the nature of the political relationship between Megawati Soekarnoputri and Hamzah Haz, representing the nationalist PDIP and the Islamic PPP respectively. The aim of this research is to analyse the form of elite compromise that occurred in the formation of national leadership in 2001. The research employs a qualitative case study design, involving document and media analysis and in-depth interviews with key informants. The findings indicate that the Megawati–Hamzah Haz relationship reflected an elite settlement through rapid compromise, a shared understanding of the rules of political competition, and mutual security guarantees between elites. In conclusion, the 2001 settlement arose from pragmatic calculations rather than ideological convergence, and played a role in creating political stability until 2004.